COMMUNITY BEHAVIOR IN MANAGING WASTE (CASE STUDY IN EAST PENFUI VILLAGE RT 09 RW 03, CENTRAL KUPANG DISTRICT) - Tamara Nensi Hersina Tobe; Aris Lambe; Jim Briand Kolianan; Blajan Konradus (Jurnal Pluralis, 2024)
This research focuses on the behavior of the people of East Penfui Village, especially RT 09 RW 03, in managing waste. The problem raised is the waste management process carried out by the community individually in each household. The research aims to determine and describe community behavior in managing waste. The method used is descriptive qualitative with purposive sampling technique. There were ten informants, consisting of the head of RT, head of RW, and residents. The results showed five out of eight informants had managed waste well, such as making fertilizer from leaves, collecting used bottles and paper to sell. The other five only collected rubbish and burned it in the yard. Suggestions that can be given are providing socialization of waste management to each household, allocating a budget for making adequate trash cans, and setting sanctions for those who do not comply with the rules.